Intraguild predation on Trichogramma chilonis Ishii (Hymenoptera: Trichogrammatidae) by the generalist predator Geocoris ochropterus Fieber (Hemiptera: Geocoridae) - Richa Varshney; Chandish R. Ballal (Egyptian Journal of Biological Pest Control, 2018)
Abstract Intraguild predation (IGP) is common in food web when two natural enemies share the same resources and prey. It may affect the success or failure of a biological control attempt. The role of intraguild predation by Geocoris ochropterus Fieber (Heteroptera: Geocoridae) on Trichogramma chilonis Ishii (Hymenoptera: Trichogrammatidae) developed on eggs of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) and Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) was evaluated under laboratory conditions. In choice experiments, both fifth instar nymph and adult of G. ochropterus preferred to predate on unparasitized eggs of H. armigera and C. cephalonica over parasitized eggs. In no-choice experiments, G. ochropterus nymph consumed 58 and 67% of unparasitized H. armigera and C. cephalonica eggs, compared to 3.33 and 7.38% of parasitized ones. A similar trend was observed in no-choice experiments with adult predator. Additional semi-field and field studies are required to explicate the consequences and intensity of intraguild predation in agro-ecosystem.